Radical Judaism : rethinking God and tradition - Green, Arthur, 1941- (Franz Rosenzweig lecture series., 2010)
How do we articulate a religious vision that embraces evolution and human authorship of Scripture? Drawing on the Jewish mystical traditions of Kabbalah and Hasidism, path-breaking Jewish scholar Arthur Green argues that a neomystical perspective can help us to reframe these realities, so they may yet be viewed as dwelling places of the sacred. In doing so, he rethinks such concepts as God, the origins and meaning of existence, human nature, and revelation to construct a new Judaism for the twenty-first century.